Capacidad antioxidante del yogurt natural suplementado con Actinidia deliciosa (kiwi) en 2,2-difenil-1-picrilhidrazilo - Quezada Camacho, Roxana Patricia (2019)
The objective of this work was to determine the antioxidant capacity of natural yogurt supplemented with Actinidia deliciosa (kiwi) against the 2,2-diphenyl-picrylhydrazyl radical (DPPH *), yogurt was elaborated using Lactobacilus bulgaricus and lyophilized Streptoccoccus thermophillus, jelly was added kiwi at 5%, 10%, 15% and 20%, was stored at 4 ° C. The determination of the antioxidant activity was done by the method of Brand Williams. The results were expressed in mg of ascorbic acid per 100 mL of fresh milk; was found in the white group 1.79; 11.03; 53.45; 85.86 and 174.17 mg AA / 100 mL in the samples at 5, 10, 15 and 20%, respectively. The IC50 was also determined, with 2,142 ug / ml in the white group and 1,852; 1.017; 0.899; 0.483 ug / ml in the samples at 5.10, 15 and 20% respectively. It is concluded that the natural yogurt supplemented with Actinidia deliciosa (Kiwi) at 20% presents greater antioxidant activity with a percentage of free radical uptake of 91.76%, proving that as the concentration increases also increases the antioxidant capacity